Green Management of Postharvest Anthracnose Caused by Colletotrichum gloeosporioides - Yeimmy Peralta-Ruiz; Chiara Rossi; Carlos David Grande-Tovar; Clemencia Chaves-López (Journal of Fungi, 2023)
Fruits and vegetables are constantly affected by postharvest diseases, of which anthracnose is one of the most severe and is caused by diverse Colletotrichum species, mainly C. gloeosporioides. In the last few decades, chemical fungicides have been the primary approach to anthracnose control. However, recent trends and regulations have sought to limit the use of these substances. Greener management includes a group of sustainable alternatives that use natural substances and microorganisms to control postharvest fungi. This comprehensive review of contemporary research presents various sustainable alternatives to C. gloeosporioides postharvest control in vitro and in situ, ranging from the use of biopolymers, essential oils, and antagonistic microorganisms to cultivar resistance. Strategies such as encapsulation, biofilms, coatings, compounds secreted, antibiotics, and lytic enzyme production by microorganisms are revised. Finally, the potential effects of climate change on C. gloeosporioides and anthracnose disease are explored. Greener management can provide a possible replacement for the conventional approach of using chemical fungicides for anthracnose postharvest control. It presents diverse methodologies that are not mutually exclusive and can be in tune with the needs and interests of new consumers and the environment. Overall, developing or using these alternatives has strong potential for improving sustainability and addressing the challenges generated by climate change.